HLA‐DRB1, ‐DRB3, ‐DRB4 and ‐DRB5 genotyping at a super‐high resolution level by long range PCR and high‐throughput sequencing. Issue 1 (30th November 2013) - Ozaki, Y.; Suzuki, S.; Shigenari, A.; Okudaira, Y.; Kikkawa, E.; Oka, A.; Ota, M.; Mitsunaga, S.; Kulski, J. K.; Inoko, H.; Shiina, T.
Abstract Super high‐resolution single molecule sequence‐based typing (SS‐SBT) is a human leukocyte antigen (HLA) DNA typing method to the field 4 level of allelic resolution (formerly known as eight‐digit typing) to efficiently detect new and null alleles without phase ambiguity by combination of long ranged polymerase chain reaction (PCR) amplification and next‐generation sequencing (NGS) technologies. We previously reported the development and application of the SS‐SBT method for the eight classical HLA loci, A, B, C, DRB1, DQA1, DQB1, DPA1 and DPB1. In this article, we describe the development of the SS‐SBT method for three DRB1 linked loci, DRB3, DRB4 and DRB5 (DRB3/4/5) and characterization of DRB1‐DRB3/4/5 haplotype structures to the field 4 level. Locus specific PCR primers for DRB3/4/5 were designed to amplify the gene regions from intron 1 to exon 6 [3′ untranslated region (3′UTR)]. In total 20 DRB1 and 13 DRB3/4/5 allele sequences were determined by the SS‐SBT to the field 4 level without phase ambiguity using 19 DR51, DR52 and DR53 positive genomic DNA samples obtained from Japanese. Moreover, 18 DRB1‐DRB3/4/5 haplotypes were estimated to the field 4 level by the SS‐SBT method in contrast to 10 haplotypes estimated by conventional methods to the field 1 level (formerly known as two digit typing). Therefore, DRB1‐DRB3/4/5 haplotyping by SS‐SBT is expected to provide informative data for improved HLA matching in medical research, transplantation procedures, HLA‐related disease studies and human population diversity studies.